Oral health knowledge and behavior among male health sciences college students in Kuwait - Honkala Sisko; Honkala Eino; Al-Ansari Jassem (BMC, 2003)
Abstract Background Health auxiliary personnel have an important role in oral health promotion when they graduate and start working in the health care system. This study aims to find out oral health knowledge and oral health behavior of male Health Sciences College students. Methods A questionnaire was distributed to all students at the male Health Sciences College in Kuwait (N = 153) during the academic year 2001/2002. The students filled the anonymous questionnaire in the class after the lecture. The response rate was 84% (n = 128). The questions consisted information on the general background, oral health behavior and oral health knowledge. Results Oral health knowledge seemed to be limited and very few background factors were associated with it. More than half of the students had visited a dentist during the previous 12 months, but only one third of students were brushing twice a day or more often. Conclusions It may be concluded that the male Health Sciences College students seemed to have appropriate knowledge on some oral health topics, but limited knowledge on the others. Their toothbrushing practices are still far behind the international recommendation (twice a day) and also the knowledge, why it should be done so frequently also very limited.